2013
DOI: 10.1096/fj.13-232215
|View full text |Cite
|
Sign up to set email alerts
|

LGR4 expressed in uterine epithelium is necessary for uterine gland development and contributes to decidualization in mice

Abstract: In previous work we generated mice with a tissue specific ablation of a leucine-rich repeat containing G-protein-coupled receptor 4 (Lgr4) using the Keratin-5 (K5) Cre transgenic mouse strain (Lgr4(K5 KO)). Interestingly, the Lgr4(K5 KO) female mice were subfertile, and their embryos had impaired development. Notably, the contributions of uterine development to the subfertility phenotype were not elucidated in the previous report. In a readdress, the following study explores uterine aberration in Lgr4(K5 KO) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…A recent study using an epithelial cell specific (Keratin-5 Cre) knockout of Lgr4 in female mice resulted in subfertility due to alterations of epithelial differentiation characterized by a reduced uterine gland number (30,44). Since the phenotype of female reproduction is more severe in total LGR4 knockout mice than the epithelial cell specific knockout mice, it suggests that LGR4 plays critical roles in other organs besides the reproductive tracts.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using an epithelial cell specific (Keratin-5 Cre) knockout of Lgr4 in female mice resulted in subfertility due to alterations of epithelial differentiation characterized by a reduced uterine gland number (30,44). Since the phenotype of female reproduction is more severe in total LGR4 knockout mice than the epithelial cell specific knockout mice, it suggests that LGR4 plays critical roles in other organs besides the reproductive tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Most animals that survived until birth died in the first days after Kato et al 2006). Neonatal null mice displayed a variety of abnormalities: male infertility Hoshii et al 2007;Li et al 2010;Mohri et al 2010;Qian et al 2013), impaired prostate development , defective uterine development (Sone et al 2013), delayed development of mammary ducts Wang et al 2013c), severe abnormalities in the anterior segment of the eye (Song et al 2008;Weng et al 2008), abnormal erythropoiesis (Song et al 2008), defective osteoblast differentiation (Luo et al 2009), renal defects (Kato et al 2006;Mohri et al 2011), defective development of the gall bladder (Yamashita et al 2009), eye-open phenotype (Kato et al 2007;Jin et al 2008), and abnormalities in hair follicle development (Mohri et al 2008). In addition, ablation of Lgr4 in mice appears to promote the white-to-brown fat switch, leading to energy expenditure (Wang et al 2013b).…”
Section: Lgr5 Marks Intestinal Stem Cellsmentioning
confidence: 99%
“…In vivo studies have demonstrated that this receptor plays an essential role during development as Lgr4-deficient embryos display embryonic and perinatal lethality [12]. Moreover, developmental defects have been reported for homozygous mice in many organs, including among others, altered tubulogenesis, impaired branching morphogenesis, renal hypoplasia, corneal dysgenesis or gallbladder agenesis [13][14][15][16][17][18][19][20][21][22][23][24][25]. In line with expression of Lgr4 in progenitors/stem cells, its deficiency generally correlates with reduced cell proliferation in tissues [7,15,19,23,[26][27][28][29].…”
Section: Tissue Expression and In Vivo Functionmentioning
confidence: 93%